Aspek Sosial dalam Novel Tanah Para Bandit Karya Tere Liye dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia - Rizkika Akromah; Mulyadi Eko Purnomo (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to analyze the social aspects in Tere Liye's novel 'Tanah Para Bandit' and their implications for Indonesian language learning. The method used in this research is descriptive qualitative method. The research data consists of dialogues sourced from the novel. The data collection technique used in this research is the listening and note-taking technique. The steps of data analysis are reading the entire novel, identifying data related to social aspects, classifying data, interpreting data, and implementing it in Indonesian language learning. Based on the results of the analysis, there are 98 data on social aspects, including 35 data on culture which includes beliefs, symbols, arts, norms, morals, politics, worldviews, 30 data on social environment which includes social relations, criminality, population, professions, social classes, and 33 data on economics which includes production, distribution, consumption, income, poverty, and lifestyle activities. The results of the research can be implemented as teaching materials in analyzing short story or novel texts in the material of developing prose appreciation with an environmental theme in Indonesian language learning at phase F or class XI for the Independent Curriculum High School. The implementation of this research is in the form of a teaching module and Student Worksheet (LKPD).